Correction: Light intensity physical activity and sedentary behavior in relation to body mass index and grip strength in older adults: cross-sectional findings from the Lifestyle Interventions and Independence for Elders (LIFE) study. - David Bann; Don Hire; Todd Manini; Rachel Cooper; Anda Botoseneanu; Mary M McDermott; Marco Pahor; Nancy W Glynn; Roger Fielding; Abby C King; Timothy Church; Walter T Ambrosius; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0116058.].